FORMATION OF ARTISTIC PERCEPTION OF FUTURE TEACHERS - Mannopovna, Jabborova Onahon; Uralovna, Jumanova Fatima; Rahmatullayevna, Mahkamova Shohida (International Journal of Psychosocial Rehabilitation, 2020)
This article is written with the aim of informing young people about all the information that they need to form their artistic perception, especially regarding artistic perception, the development of their artistic abilities and aesthetic education in the cultural education of young citizens of the country. Artistic perception is the perception of works of art. He is especially active in the study of rare artifacts and important creative events that are recognized as national art values. Therefore, increasing the role of culture in public life, we believe that artistic culture, in particular an important component of art, should be used as widely as possible in the formation of artistic perception and will stimulate future teachers to artistic perception